Fracture resistance of structurally compromised and normal endodontically treated teeth restored with different post systems: An in vitro study - Vajihesadat Mortazavi; Mohammadhossein Fathi; Najmeh Katiraei; Shirin Shahnaseri; Hamid Badrian; Navid Khalighinejad (Wolters Kluwer Medknow Publications, 2012)
Background: With the aim of developing methods that could increase the fracture resistance of structurally compromised endodontically treated teeth, this study was conducted to compare the effect of three esthetic post systems on the fracture resistance and failure modes of structurally compromised and normal roots. Materials and Methods: Forty five extracted and endodontically treated maxillary central teeth were assigned to 5 experimental groups (n=9). In two groups, the post spaces were prepared with the corresponding drills of the post systems to be restored with double taper light posts (DT.Light-Post) (group DT.N) and zirconia posts (Cosmopost) (group Zr.N). In other 3 groups thin wall canals were simulated to be restored with Double taper Light posts (DT.W), double taper Light posts and Ribbond fibers (DT+R.W) and Zirconia posts (Zr.W). After access cavity restoration and thermocycling, compressive load was applied and the fracture strength values and failure modes were evaluated. Data were analyzed using two-way ANOVA, Tukey and Fisher exact tests (P<0.05). Results: The mean failure loads (N) were 678.56, 638.22, 732.44, 603.44 and 573.67 for groups DT.N, Zr.N, DT.W, DT+R.W and Zr.w respectively. Group DT+R.W exhibited significantly higher resistance to fracture compared to groups Zr.N, DT.W and Zr.w (P<0.05). A significant difference was detected between groups DT.N and Zr.W (P=0.027). Zirconia posts showed significantly higher root fracture compared to fiber posts (P=0.004). Conclusion: The structurally compromised teeth restored with double taper light posts and Ribbond fibers showed the most fracture resistance and their strengths were comparable to those of normal roots restored with double taper light posts. More desirable fracture patterns were observed in teeth restored with fiber posts.